Multiplexed biomimetic lipid membranes on graphene by dip-pen nanolithography - Hirtz, Michael (Nature Pub. Group, 2013)
The application of graphene in sensor devices depends on the ability to appropriately functionalize the pristine graphene. Here we show the direct writing of tailored phospholipid membranes on graphene using dip-pen nanolithography. Phospholipids exhibit higher mobility on graphene compared with the commonly used silicon dioxide substrate, leading to well-spread uniform membranes. Dip-pen nanolithography allows for multiplexed assembly of phospholipid membranes of different functionalities in close proximity to each other. The membranes are stable in aqueous environments and we observe electronic doping of graphene by charged phospholipids. On the basis of these results, we propose phospholipid membranes as a route for non-covalent immobilization of various functional groups on graphene for applications in biosensing and biocatalysis. As a proof of principle, we demonstrate the specific binding of streptavidin to biotin-functionalized membranes. The combination of atomic force microscopy and binding experiments yields a consistent model for the layer organization within phospholipid stacks on graphene.